A mineralogical investigation of co-existing iron-titanium oxides from various igneous rocks with special reference to some South African titaniferous iron ores - Reynolds, Ivan Melvin (Rhodes University, Faculty of Science, Department of Geology, 1979)
Part I consists of a detailied review of the available literature on the Fe- Ti oxides and their solid solution relationships. Particular attention is glven to the microstructures exhibited by these oxides and the hypotheses put forward to explain them. These data are synthesised and models are presented in which the microstructural developments in titaniferous magnetites amd ilmenites are explained in terms of current ideas on the influence of oxygen fugacity, exsolution mechanisms and crystal chemistry. These models have direct application to the microintergrowths observed in the naturally occurring Fe-Ti oxides from a wide range of igneous rocks. The available data on the minor and trace element chemistry of the Fe-Ti oxides are reviewed with particular reference to their variation in these minerals from different host rocks. The behaviour of the Fe-Ti oxides during secondary oxidation is discussed with particular reference to the oxidation of titaniferous magnetite and the weathering of ilmenite. The results of a mineralogical investigation into the co-existing Fe-Ti oxides from a range of igneous rocks including kimberlites, gabbros, dolerites, diabases, syenites, granophyres, granites and pegmatites are presented in Part 2 together with data on the ilmenites present in certain Eastern Cape beach sands. The kimberlite ilmenites are chemically distinct and can be readily distinguished on the basis of their relatively high MgO, Fe₂0₃ and Cr₂O₃ contents. They can also be distinguished from ilmenites from other igneous rocks on the basis of unit cell dimensions, d-spacings, reflectivities and micro-indentation hardness. The ilmenites from a wide range of basic to granitic igneous rocks exhibit a limited compositional range in which the MnO content appears to increase with increasing Si0₂ content. Relatively insensitive indirectly determined parameters such as unit cell dimensions, reflectivities and micro-indentation hardnesses cannot be used to distinguish between the ilmenites from the different rock types in these classes. The titaniferous magnetites exhibit progressively decreasing Ti0₂ contents from a maximum in the basic igneous rocks to a minimum in the granitic types. The titaniferous magnetite typically exhibits varying degrees of deuteric alteration, while the microstructures developed can be interpreted 1n terms of the models presented in Part 1. Part 3 represents an extension of Part 2 and deals with a mineralogical investigation of the titaniferous iron ores in five South African basic intrusions. The Bushveld and Kaffirskraal ores consist of multi-phase titaniferous magnetite grains containing crystallographically oriented ilmenite, ulvospinel and pleonaste microintergrowths. Minor coarser-grained ilmenite is also present. The Usushwana ores are texturally similar but contain abundant lamellar ilmenite in place of the ulvospinel. The primary features are well preserved in the unmetamorphosed Bushveld and Kaffirskraal ores. The Usushwana ores have been slightly metamorphosed resulting in the extensive replacement of the titaniferous magnetites by sphene and chlorite aggregates. The ores from these three complexes cannot be beneficiated by conventional ore-dressing techniques and require direct metallurgical treatment for the recovery of Fe, Ti0₂ and V₂O₅. The metamorphosed Mambula and Rooiwater ores have been recrystallised to a varying degrees and consist of multi-phase titaniferous magnetite grains containing modified ilmenite and pleonaste microintergrowths. These modified microstructures differ from those encountered in titaniferous magnetites from unmetnmorphosed basic rocks and their degree of modification can be related to the degree of met amorphism. Variable amounts of coarse granular ilmenite are also present and their development is related to the metamorphic grade and degree of recrystallisation. These ores can be partially beneficiated to yield ilmenite- and lower-Ti0₂ magnetite concentrates in which V₂O₅ contents of the magnetic fractions are higher than those of the original ores. The Trompsburg ores differ from those of the other complexes in that they are Mg-rich and are characterised by the presence of abundant olivine. The titaniferous magnetites typically exhibit well-defined ulvospinel cloth textures and are often surrounded by small amounts of graphite. They show evidence of a variety of extensive late-stage alteration features. The ores from the five investigated complexes are compared with similar ores from the Bushveld Complex. The ores from each complex can be readily distinguished on the basis of their chemical compositions and textural relationships. These features can be related to their crystallisation his tories and, in some cases, to post-crystallisation processes. The microstructural evolution of the ores from each complex is interpreted in terms of the models developed in Part I.
Keywords: Igneous rocks; Mineralogy